Comparative transcriptional and metabolic responses of Pinus pinea to a native and a non-native Heterobasidion species. (21st August 2018) - Pepori, Alessia Lucia; Michelozzi, Marco; Santini, Alberto; Cencetti, Gabriele; Bonello, Pierluigi; Gonthier, Paolo; Sebastiani, Federico; Luchi, Nicola
Abstract: Heterobasidion irregulare is a causal agent of root and butt-rot disease in conifers, and is native to North America. In 1944 it was introduced in central Italy in a Pinus pinea stand, where it shares the same niche with the native species Heterobasidion annosum . The introduction of a non-native pathogen may have significant negative effects on a naïve host tree and the ecosystem in which it resides, requiring a better understanding of the system. We compared the spatio-temporal phenotypic, transcriptional and metabolic host responses to inoculation with the two Heterobasidion species in a large experiment with P. pinea seedlings. Differences in length of lesions at the inoculation site (IS), expression of host genes involved in lignin pathway and in cell rescue and defence, and analysis of terpenes at both IS and 12 cm above the IS (distal site, DS), were assessed at 3, 14 and 35 days post inoculation (dpi). Results clearly showed that both species elicit similar physiological and biochemical responses in P. pinea seedlings. The analysis of host transcripts and total terpenes showed differences between inoculation sites and between pathogen and mock inoculated plants. Both pathogen and mock inoculations induced antimicrobial peptide and phenylalanine ammonia-lyase overexpression at IS beginning at 3 dpi; while at DS all the analysed genes, except for peroxidase, were overexpressed at 14 dpi. A significantly higher accumulation of terpenoids was observed at 14 dpi at IS, and at 35 dpi at DS. The terpene blend at IS showed significant variation among treatments and sampling times, while no significant differences were ever observed in DS tissues. Based on our results, H. irregulare does not seem to have competitive advantages over the native species H. annosum in terms of pathogenicity towards P. pinea trees; this may explain why the non-native species has not widely spread over the 73 years since its putative year of introduction into central Italy.